Investigation of carbon dioxide capture with aqueous piperazine on a post combustion pilot plant – Part II: Parameter study and emission measurement. (June 2015) - Rabensteiner, Markus; Kinger, Gerald; Koller, Martin; Gronald, Günter; Hochenauer, Christoph
Highlights: The pilot plant allows a practical operation. Operation with real flue gases of the gas- and coal-fired power plant. Absorber and desorber have nearly industrial heights. Advantages of piperazine over monoethanolamine can be identified. Positive effects of high flue gas flow rates and desorber pressures. Abstract: This paper continues the investigation of a 37.6 wt% piperazine solution (7 molal) in a PCC-test facility on the power plant in Dürnrohr, Austria. The use of real power plant flue gas and the well-conceived dimensions of the test facility enable industry-related conditions for full scale applications. A minimum specific energy for solvent regeneration of 3.17 GJ/ t CO 2 was determined in Part I of this paper. The optimal solvent flow rate is 20% lower in comparison to that of 30 wt% MEA. Part II tries to reduce the energy consumption further by carrying out a detailed parameter study. Especially at high flue gas flow rates, piperazine shows a good performance because of its fast kinetics. If the maximum achievable flue gas flow rate of 120 m 3 /h (F-factor ∼2 Pa 0.5 ) is set, the specific energy for solvent regeneration drops to 3 GJ/ t CO 2 . The fast kinetics has also a positive effect by reduction of the absorber height. Halving the absorber height still allows a performance similar to that of 30 wt% MEA. Due to the high thermal stability, piperazine enables an operation with high desorber pressures. Higher desorber pressures, resulting in a lower CO2 compression work. In addition, the regeneration energy can be further reduced. An energy saving can also be achieved by the temperature reduction of the incoming flue gas. By operation with flue gases of a natural gas-fired boiler, the minimal energy consumption rises to 3.6 GJ/ t CO 2 . The optimal solvent flow rate decreases as with 30 wt% MEA. An emission measurement shows a direct correlation between NH3 concentration of the treated flue gas and the solvent flow rate. Because of low water circulation in the water washing section, the NH3 emissions in the treated flue gas increase at high solvent flow rates.